THE FORMATION OF THE FUTURE GEOGRAPHY TEACHERS’ RESEARCH SKILLS DURING THE STUDY OF THE BASICS OF LANDSCAPE - Dudka, Ynna H. (Educological discourse, 2014)
The formation of the future geography teachers’ research skills has been one of the most important tasks of the educational process in universities and is becoming particularly significant in today’s socio-economic transformations. The Pedagogy and Methods of Secondary Education: Geography professional training program includes the Basics of Landscape course that aims to develop the knowledge and skills required for geography teachers to manage the studies, teach the theoretical fundamentals of Landscape, a synthetic, integrated physical geography section, develop a system of geographical thinking, comprehensive vision and understanding of nature the earth surface.